Design of internet of things (IoT) based website for quality monitoring of home organic compost - Angela Stera Mentari; Rita Purnamasari; Yulinda Eliskar (Universitas Telkom, 2026)
Waste is the residual product of human use that is often simply discarded and piled up, including organic household waste. The decomposition of organic waste causes unpleasant odors, environmental pollution, and becomes a breeding ground for disease-carrying animals. Therefore, composting is a necessary method that can be applied in households to manage organic waste with the aim of reducing and transforming it into beneficial products. In this modern era, a more efficient composting tool is needed, utilizing the Internet of Things (IoT) to monitor the composting process in real-time to produce compost that meets the Indonesian National Standard 19-7030-2004. This compost quality monitoring can be conducted both locally and remotely through a website integrated with the NodeMCU ESP32 microcontroller, which is connected to a Wi-Fi network to transmit data in real-time to a MySQL database for storage and management. Website testing at Wi-Fi distances of 5 meters and 10 meters from the device resulted in average response times of 31.943 ms and 31.444 ms, respectively, indicating that the website receives information with very good speed. 99.33% of all respondents agreed that the website met the friendly criteria in terms of both color and layout.